INDIRECTNESS IN THE COMMUNICATION OF PROSTITUTES IN SURABAYA - Saputro, Suswanto Ismadi Megah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
This research aims to identify how the prostitutes communicate to their clients in Surabaya. The data were obtained from the real communication occurring among the prostitutes’ and the clients. It was found that Indonesian language is dominantly used in the communication compared to Javanese language. This is due to the fact that Javanese language is more complicated having different speech levels based on the social status of the speakers. Furthermore, the research showed that the prostitutes tend to use euphemism in their service. The euphemism is part of the style of Javanese prostitutes performing indirectness as a part of Javanese culture.